Automated Image Inpainting for Historical Artifact Restoration Using Deep Generative Models - Baggam Swathi (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Historical artifacts often suffer degradation due to aging, environmental exposure, and mishandling, leading to partial loss of visual content. Manual restoration is time-consuming, expertise-driven, and prone to subjectivity. Automated image inpainting techniques using deep generative models provide a scalable solution for artifact preservation by reconstructing missing regions with semantically consistent content. In this paper, we propose a generative adversarial network (GAN)-based approach for historical artifact restoration, capable of capturing both global structures and fine textures. The model integrates perceptual loss, adversarial loss, and structural similarity constraints to ensure high-fidelity reconstructions. Experimental results on benchmark datasets demonstrate superior performance compared to conventional inpainting methods, with improvements in Peak Signal-to-Noise Ratio (PSNR), Structural Similarity Index (SSIM), and Fréchet Inception Distance (FID). Furthermore, we provide a case study on digitized cultural heritage artifacts, showcasing the potential of our approach in museum preservation and archival digitization. <!--StartFragment -->DOI: https://doi.org/10.17762/ijisae.v12i7s.7878<!--EndFragment -->